2015
DOI: 10.1242/jcs.171165
|View full text |Cite
|
Sign up to set email alerts
|

STX13 regulates cargo delivery from recycling endosomes during melanosome biogenesis

Abstract: Melanosomes are a class of lysosome-related organelles produced by melanocytes. Biogenesis of melanosomes requires the transport of melanin-synthesizing enzymes from tubular recycling endosomes to maturing melanosomes. The SNARE proteins involved in these transport or fusion steps have been poorly studied. We found that depletion of syntaxin 13 (STX13, also known as STX12), a recycling endosomal Qa-SNARE, inhibits pigment granule maturation in melanocytes by rerouting the melanosomal proteins such as TYR and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 56 publications
4
74
0
3
Order By: Relevance
“…These findings suggest that Rab22A regulates the T N and T L of KIF13A‐positive REs similar to the MHC‐1‐positive tubules shown previously . Additionally, subcellular membrane fractionation showed that Rab22A was enriched in the membrane (1–1.4 M sucrose) fractions positive for the RE markers STX13 , KIF13A and AP‐1 (Fig D). As a control, the membrane fractions were also probed for other organelle‐specific makers such as GM130 ( cis ‐Golgi), LIMPII (LE and TGN) and LAMP‐2 (lysosome) (Fig D).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…These findings suggest that Rab22A regulates the T N and T L of KIF13A‐positive REs similar to the MHC‐1‐positive tubules shown previously . Additionally, subcellular membrane fractionation showed that Rab22A was enriched in the membrane (1–1.4 M sucrose) fractions positive for the RE markers STX13 , KIF13A and AP‐1 (Fig D). As a control, the membrane fractions were also probed for other organelle‐specific makers such as GM130 ( cis ‐Golgi), LIMPII (LE and TGN) and LAMP‐2 (lysosome) (Fig D).…”
Section: Resultssupporting
confidence: 80%
“…This was supported by live cell imaging experiments, where a cohort of TYRP1‐GFP localized to the RFP‐STX13‐positive vacuolar endosomes in Rab22A‐depleted melanocytes (Fig EV4A). As expected, TYRP1‐GFP in control melanocytes localized majorly to the melanosomes while a small cohort to the RFP‐STX13‐positive endosomes or tubular structures (Fig EV4A) similar to other melanocytic cargoes . Immunoblotting analyses showed that TYRP1, ATP7A and TYR (tyrosinase) protein levels were dramatically reduced, while the proteolytic processing of PMEL (full length (P1) into Mβ) was moderately affected in Rab22A‐depleted melanocytes compared to control cells (Fig C).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…2b). It contained 16 genes, 1 of which, STX12, affects pigmentation by involvement in melanosome trafficking34. LRP5 , described above for the cornix – orientalis contact zone, was located in an outlier window and also associated with divergent cacti (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…STX12 is localized in early and recycling endosomes as well as the plasma membrane, and interacts with the t-SNARE proteins syntaxin 6 and Vti1a and the v-SNARE protein VAMP4 and the formed complex is responsible for the homotypic fusion of early endosomes [51,52]. Furthermore, it has been suggested that STX12 can function at the plasma membrane and can regulate membrane fusion and recycling of plasma membrane proteins [63]. The N-terminal Habc regulatory interacts intramolecularly with the SNARE domain, rendering the protein to a "closed conformation" and prohibiting the interaction with the cognate partners and the assembly of the SNARE complex [64][65][66].…”
Section: Discussionmentioning
confidence: 99%